Analisis Kesulitan Belajar Matematika Pada Siswa Kelas II di SDN Dian Andalas - Ari Suriani; Yuspita Yuspita (GLOBAL SCIENTS PUBLISHER, 2025)
This research is motivated by the fact that many grade II students at SDN Dian Andalas have difficulty learning math. The purpose of this research is to find out the causes of students having difficulty learning math, the factors that influence math learning difficulties, and the efforts made to overcome math learning difficulties. This research uses qualitative data obtained through direct interview techniques with the research sample. The results showed that 75% of grade II students at SDN Dian Adalas had difficulty learning mathematics, especially understanding the basic concepts of calculation operations. Math learning difficulties are caused by internal factors and external factors. Efforts made by students to overcome difficulties are by independent learning, asking teachers, asking parents for help, studying in groups and attending tutoring